An Efficient Dynamic Modeling Technique for a Central Tie Rod Rotor - Jingze Liu; Qingguo Fei; Shaoqing Wu; Zhenhuan Tang; Sanfeng Liao; Dahai Zhang (International Journal of Aerospace Engineering)
Compared with the three-dimensional rotor model for a central tie rod rotor, an equivalent one-dimensional model can greatly improve the computational efficiency in rotor dynamics analysis with a certain accuracy. However, little research work can be found on improving the modeling accuracy of one-dimensional models using experimental data. In this paper, a one-dimensional discrete mass model considering pretightening force is proposed for central tie rod rotors to achieve the purpose of both efficient and accurate modeling. Experimental testing and three-dimensional model analysis are used as reference and verification approaches. A sensitivity-based method is adopted to update the proposed one-dimensional model via minimizing the error in the critical speed comparing with the corresponding three-dimensional finite element model which has been verified by a modal test. Prediction of damped unbalanced response is conducted to show the practicality of the updated one-dimensional model. Results show that the method presented in this research work can be used to simulate a complex preloaded rotor system with high efficiency and accuracy.